Sustainability-based Agroindustry Business Model for Local Economic Strengthening - Judijanto, Loso; Widiarta, I Putu Gede Didik; Wahyuni, Ira (Westscience Press, 2025)
This study examines the role of sustainability-based agroindustry business models in strengthening the local economy in Indonesia. Using a quantitative approach, data were collected from 100 respondents via a Likert scale questionnaire and analyzed with Structural Equation Modeling - Partial Least Squares (SEM-PLS). The findings reveal that environmental sustainability (β = 0.35, p < 0.01), economic viability (β = 0.45, p < 0.01), and social equity (β = 0.28, p < 0.05) significantly contribute to local economic strengthening. The model explains 65% of the variance in the local economy, underscoring the importance of a balanced approach to sustainability. This study highlights the practical and policy implications of adopting sustainable practices in agroindustry, emphasizing the need for stakeholder collaboration, government support, and community engagement to foster economic and environmental resilience.